2000
DOI: 10.4141/s99-054
|View full text |Cite
|
Sign up to set email alerts
|

Soil aeration for dairy manure spreading on forage: Effects on ammonia volatilisation and yield

Abstract: , J. 2000. Soil aeration for dairy manure spreading on forage: Effects on ammonia volatilisation and yield. Can. J. Soil Sci. 80: 319-326. Experiments were conducted to evaluate the effects of performing soil aeration either before or after spreading liquid manure in forage production systems. The experiments included eight trials performed in 1996 using a non-interfering diffusion method to determine ammonia (NH 3 ) flux emissions from both aerated and control plots. For all eight trials, the manure applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 19 publications
2
34
1
Order By: Relevance
“…This is similar to the findings of Gordon et al (2000), who reported no difference in NH 3 volatilization when using the Aerway equipment for incorporation vs. surface application. However, in the study by Gordon et al (2000), the Aerway was used either before slurry application or after, whereas in the present study the manure was applied immediately before the tines of the Aerway system. Contrary to the present findings, Bittman et al (2005) reported a 48% reduction in NH 3 emissions with Aerway incorporation vs. surface application of liquid dairy manure.…”
Section: Resultssupporting
confidence: 81%
“…This is similar to the findings of Gordon et al (2000), who reported no difference in NH 3 volatilization when using the Aerway equipment for incorporation vs. surface application. However, in the study by Gordon et al (2000), the Aerway was used either before slurry application or after, whereas in the present study the manure was applied immediately before the tines of the Aerway system. Contrary to the present findings, Bittman et al (2005) reported a 48% reduction in NH 3 emissions with Aerway incorporation vs. surface application of liquid dairy manure.…”
Section: Resultssupporting
confidence: 81%
“…Phillips et al (1990) reported large losses of NH 3 (and production of odour) when slurry was sprayed into air, which was significantly reduced by soil injection or using hanging/trailing hoses. Gordon et al (2000) reported only a small benefit of soil aeration (in pasture) on reducing NH 3 loss, but found aeration also reduced grass yield. In their study, an aerator was used that created slots 1.5 cm wide, 15 cm long and 15 to 20 cm deep.…”
mentioning
confidence: 99%
“…Some nutrients, particularly N, however, may be lost to the atmosphere after land application; thereby reducing the value of the manure and contributing to environmental degradation (Gordon et al 2000). Up to 90% of applied ammoniumnitrogen (NH 4 ' -N) in manure can be lost through ammonia (NH 3 ) volatilization (Wulf et al 2002).…”
mentioning
confidence: 99%